Health risks of tobacco use and awareness of graphic health warnings: findings from a community study in urban Patna - Shishir Kumar, Dr Shishir Kumar; Dr. Shivani Agrawal; Dr. Nidhi Prasad; Dr. Navin Mishra; Dr. Sanjay Kumar (Social Determinants of Health, 2025)
Background: Tobacco consumption remains a foremost cause of preventable illness and death worldwide. A study analyzing NFHS-5 and GATS-2 data indicates that men's tobacco usage in urban areas declined from 38.9% to 25.4% between NFHS-4 and NFHS-5, while women's usage decreased from 4.4% to 3.3%. These findings suggest a positive trend in reducing tobacco consumption in urban regions.To evaluate the patterns of using tobacco and assess the awareness of graphic health warnings among tobacco users in urban Patna, focusing on their understanding of health risks associated with tobacco. Methods: 224 tobacco users in the urban Patna community participated in this 12-month cross-sectional study. Purposive sampling was used to choose the participants, and a pre-designed, pre-tested questionnaire was used for the interviews. PSPP software was used to analyze the data using frequency and percentages. Results: Mean age of the participants was 38.12 ± 12.087. Out of 224 participants, majority of the participants use smokeless tobacco form. 89.2% participants said pictorial + written warnings are more understandable but 86.5% did not know which kind of warning has more impact on smokers. Conclusion: Despite growing awareness of health risks, tobacco use remains prevalent due to various socioeconomic and cultural factors, highlighting the need for more effective public health interventions.